PENGARUH PEMBELAJARAN PRAKTIKUM, PERAN DOSEN, DAN PELATIHAN BREVET PAJAK TERHADAP KEMAMPUAN MENYUSUN SURAT PEMBERITAHUAN (SPT)(Studi Kasus Pada Mahasiswa Akuntansi Universitas Sarjanawiyata Tamansiswa Yogyakarta) - Mareta Wulandari; Andri Waskita Aji, Suyanto (CV. ADIBA AISHA AMIRA, 2024)
The method used in this study is a quantitative descriptive method with primary data types obtained by distributing questionnaires online to respondents via the Google form. From this distribution, a sample of 110 accounting students from Class of 2019 at Sarjanawiyata Tamansiswa University was obtained using a random sampling technique. This data was processed using the SPSS program version 25. Based on data processing that has been done, the results of this study show that, 1) the effect of practicum learning has no effect on the ability to prepare SPT, 2) the role of the lecturer has no effect on the ability to prepare SPT, 3) Tax brevet training has a positive effect on the ability to prepare SPT. while practicum learning, the role of lecturers, and tax brevet training together have a significant effect on the ability to prepare SPT